2022
DOI: 10.1088/1674-1056/ac6014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesoscale eddies on the spatial coherence of a middle range sound field in deep water

Abstract: The mesoscale eddies have a remarkable influence on the sound field underwater, and many previous studies investigate the effects of eddies on transmission loss (TL), convergence zone, time delay, etc. However, the effects of eddies on spatial coherence are less studied and remain unclear. In this paper, the effects of eddies on spatial coherence at the subsurface in deep water is investigated. The eddy environments are simulated with Gaussian eddy equations, the complex pressure field is obtained using a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In the last decade, ocean-acoustic remote sensing has been trying to use acoustic models to better analyze the effects of mesoscale eddies on acoustic propagation, and the most common models usually include simple normal wave models [7], parabolic equation models [8], fast field models [9], ray models [10], etc. These models are based on a certain simplification of the actual problem and are obtained by making a reasonable approximation to the solution of the fluctuation equations.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, ocean-acoustic remote sensing has been trying to use acoustic models to better analyze the effects of mesoscale eddies on acoustic propagation, and the most common models usually include simple normal wave models [7], parabolic equation models [8], fast field models [9], ray models [10], etc. These models are based on a certain simplification of the actual problem and are obtained by making a reasonable approximation to the solution of the fluctuation equations.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al [18] focused on the influence of warm eddies in the Gulf of Mexico on sound propagation, observing the alteration in sound propagation paths, the expansion of convergence zones (CZs), and the dispersion of energy. Gao et al delved into the spatial correlation in warm and cold eddies, elucidating the correlation mechanism using ray theory [19]. While current research about the influence of eddies on sound propagation characteristics primarily concentrates on energy changes [20][21][22], there is an absence of comprehensive investigations into the spatial correlation of the sound field and its impact on the array gain.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2021a) analyzed a cyclonic eddy that was found in the Pacific Northwest to investigate the effect of eddy on the coupling coefficient of various orders of normal modes. Gao et al (2022) investigated the effects of the eddy on horizontal and vertical spatial coherence in deep water with the Gaussian eddy model presented by Calado et al (2006). However, due to the movements of eddies, their corresponding acoustics observation data need to be measured through specialized design experiments.…”
Section: Introductionmentioning
confidence: 99%